Effectiveness of intensive short-term dynamic psychotherapy on depression and sleep disorders in women afflicted by migraine: a multi base line single-subject study (Development Engineering Conferences Center Articles Database, 2024)
Migraine and its effects on depression and sleep disorders are among the most crucial subjects in psychology. In this regard, exploring and examining different psychological methods and their effectiveness on migraine and related indirect damages seem momentous. Current study is conducted to measure the effectiveness of intensive short-term dynamic psychotherapy on the abovementioned subject. This method is done by a multi base line single-subject study on a statistical population which consists of female patients who have migraine and referred to Sabzevar Vasei Hospital during a one-year period from 2023 to 2024. A sample of two women were examined in separate therapy sessions using Beck anxiety questionnaire and revised McGill pain questionnaire. Within and between situation analysis were used in SPSS27 and Excel to interpret the results. Results show that intensive short-term dynamic psychotherapy has a significant effect on depression (went up 52.86% for intervention to base and 59.11% for follow-up to base) and sleep disorders (went up 62.79% for intervention to base and 80.73% for follow-up to base). Results were examined by Cohen’s d revealed that the effectiveness of intensive short-term dynamic psychotherapy is high in intervention and average in follow-up stages for depression. Also, high for both stages regarding sleep disorders. Furthermore, within and between analyses revealed a meaningful difference between base and intervention stages for both samples (PND=100). Measurements and examinations showed the durability of this psychological method thorough follow-up stage.